TESTING THE FLEXURAL PROPERTIES OF POLYMER COMPOSITES FOAMING HYBRID OIL PALM EMPTY FRUIT BUNCHES (OPEFB) AND ZINC OXIDE (ZnO) - Adlie, Taufan Arif; Rizal, Samsul; Ali, Nurdin; Huzni, Syifaul; Arif, Zainal; Suheri, Suheri (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2020)
Oil palm empty fruit bunches (OPEFB) is one of the palm oil industry solid wastes that can be used as an alternative material to product composites. This research was conducted to determine the effect of the addition of Zinc Oxide (ZnO) as a filler material hybridized with OPEFB fiber to the flexural strength of polymeric foam composites. The aim of this research is to obtain the strength of the flexural test value of the composite material polymeric foam reinforced OPEFB fiber and Zinc Oxide (ZnO) with reference to the ASTM D790-92 standard. The composition of the specimens are 70% Resin, 15% OPEFB Fiber, 15% Polyurethane with different fiber sizes namely mesh (40, 60, 80, 100) and the addition of Zinc Oxide (ZnO) of (0%, 5%, 10%, 15%, 20%). The test specimen used for each composition is 5 samples, so that the entire test sample is 100 samples. From the test data it can be concluded the value of flexural strength in the 100 mesh OPEFB specimens and the addition of Zinc Oxide (ZnO) 10% is the best composition compared to 40, 60 and 80 mesh OPEFB with the addition of Zinc Oxide (ZnO) 5%, 15%, and 20%, where the voltage value is 10,01141 MPa and the strain value is 0,898456 mm / mm. From the research data it can also be concluded that the smaller the OPEFB fiber size with the addition of zinc oxidation (ZnO) 10%, the flexural strength of the polymeric foam composite material will be better.